KEJAHATAN TERHADAP ANAK DAN SOLUSINYA MENURUT HUKUM ISLAM - NURWAHIDAH, NURWAHIDAH (Syariah: Jurnal Hukum dan Pemikiran, 2015)
Children should live a life that is safe and comfortable with their parents and nanny. But the fact is happening, children often face persecution, violence, beatings and harassment, which often lead to death. Islamic law set some rules that may be subject to criminal perpetrators of violence against children committed by parents themselves, not others, while punishment requires an equal position between the perpetrators to the victim. There are scholars argue parents remain exposed qishash, and other scholars argue there is no qishash, just tazir and parents lose their right to inherit property. A lot of cases that occurred in the community in a variety of species, and most perpetrators have been sentenced. However the case that appears only a small part are revealed. In the midst of such conditions should be enforced once hadhanah principles stipulated in Islamic law. Hadhanah emphasize parenting to parents and close family, so that children can be cared for with love and responsibility. So the lives and safety of children will be more secure and protected.